Perioperative Medicine - Hamilton, Mark; Mythen, Monty
Perioperative Medicine is an open access journal that publishes highly topical clinical research relating to the perioperative care of surgical patients. Its essence is the distillation, examination and application of clinical evidence to improve surgical outcome. Modern perioperative medicine is a true multidisciplinary speciality and the journal welcomes research in all areas relevant to perioperative medicine from any healthcare professional. Main areas of interest include but are not limited to: Perioperative outcomes (surgical, anesthetic, medical) Evidence-based care Perioperative guidelines and consensus statements Preoperative evaluation and risk scores Preoperative testing Cardiopulmonary exercise testing Perioperative decision making Perioperative haemodynamic monitoring Surgical optimization and enhanced surgical recovery programs Perioperative fluid management.